BACTERIAL LEACHING OF THE METALS FROM THE SPENT MASS OF FUEL ELEMENTS - Н. Ю. Васильєва; Л. І. Слюсаренко; Л. С. Нещерет; К. І. Семенов; Т. В. Васильєва; І. А. Блайда (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2018)
Aim. To establish the possibility of bacterial leaching of zinc and manganese from the electrode mass of spent batteries. Methods. To determine the growth of acidophilic chemolithotrophic bacteria of acidophilic chemolithotrophic bacteria(ACB) there were used the media of different component and concentration composition. Ferrous iron and thiosulfate were used as energy sources. The amount of cells was determined by seeding on solid medium after tenfold serial dilutions. Stained microscopic preparation was examined by light microscopy. The method of atomic absorption spectroscopy with using AAS-1, S-115PK Selmi instruments was used to determine the content of metals in solutions. The results of determining the structural analysis of the electrode mass of spent batteries were recorded on a URS-50IM diffractometer. Results. The possibility of using AHB for leaching manganese and zinc from the electrode mass of spent batteries was established. The maximum metal leaching within a week was recorded when there were used the media 9K1 with ferrous iron at concentration of 44.5 g/dm3. When extending the term of leaching to a forthnight there were registered high intensity of biological leaching of the metals from electrode mass of spent batteries only in case of using the nutrient medium No. 15. It was shown that the using of the suspension Acidithiobacillus ferroooxidans MF Lv 7 increases the degree of manganese extraction to 30.0%, and zinc to 99.8%. The differences in the structure of the electrode mass of spent batteries before and after bacterial leaching, namely the absence of ZnO and MnO, decrease in the amount of MnO2, increase in Mn2O3, and appearance of Mn3O4 has been shown with help of X-ray diffraction analysis. Conclusions. The possibility of using ACV for bacterial leaching of metals from the electrode mass of spent batteries was shown. The obtained results make it possible to additionally getting zinc and manganese and preventing environmental pollution by environmentally hazardous compounds.